Food Allergy from Infancy Through Adulthood - Sicherer, Scott H; Warren, Christopher M; Dant, Christopher; Gupta, Ruchi S; Nadeau, Kari C (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2020)
Food allergies are the result of immune responses that cause adverse reactions to foods. Immune responses to foods may produce a spectrum of symptoms and disorders, including acute allergic reactions and anaphylaxis, food protein-induced allergic proctocolitis, food protein-induced enterocolitis syndrome, food-dependent, exercise-induced anaphylaxis, and oral allergy syndrome (pollen-food allergy syndrome). Food-allergic responses also contribute to chronic inflammatory disorders such as eosinophilic esophagitis and atopic dermatitis. Although food allergy affects people from infancy through adulthood, there are allergic features that differ according to age (ie, presentation, triggers, and natural course) and have important implications for diagnosis, prognosis, and management. New food allergies can develop at any age, and we propose similarities in the etiology of de novo food allergy whether in infancy or adulthood. The approach to managing food allergy changes dramatically over the life course, and physicians and patients must respond accordingly to optimize care. Food allergy therapies are emerging, and the efficacy and safety of these interventions could differ by age group of those treated. In this review, we highlight interesting observations on the etiology and characteristics of food allergy presenting at different ages and discuss clinical management as it relates to life stage.